2021
DOI: 10.1016/j.resinv.2021.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Serum Krebs von den Lungen-6 levels are associated with mortality and severity in patients with coronavirus disease 2019

Abstract: Background The serum Krebs von den Lungen-6 (KL-6) level is a predictive factor for acute respiratory distress syndrome (ARDS). The development of ARDS has been reported in patients with coronavirus disease 2019 (COVID-19). This study aimed to determine whether serum KL-6 levels are associated with mortality and severity in patients with COVID-19. Methods Among 361 Japanese patients with COVID-19 who were hospitalized at Kanagawa Cardiovascular and Respiratory Center be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 25 publications
3
21
0
Order By: Relevance
“…According to our data, a significantly greater risk for worse outcomes should be considered for patients having a serum KL-6 value of 968 U/mL or more, with a sensitivity and specificity of 79.2% and 87.1%, respectively, and a positive predictive value of 70.4%. These findings fully match data obtained from previous studies in which elevated levels of serum KL-6 are a significant predictor of poor outcomes in patients with COVID-19 [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…According to our data, a significantly greater risk for worse outcomes should be considered for patients having a serum KL-6 value of 968 U/mL or more, with a sensitivity and specificity of 79.2% and 87.1%, respectively, and a positive predictive value of 70.4%. These findings fully match data obtained from previous studies in which elevated levels of serum KL-6 are a significant predictor of poor outcomes in patients with COVID-19 [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 90%
“…The clinical implications of serum KL‐6 and SP‐D levels have been investigated in the above‐stated context. As per reports, both serum KL‐6 and SP‐D levels are elevated in patients with severe COVID‐19 and, therefore, these constituents are useful biomarkers of disease severity 9,11,13,20,21 . In addition to disease severity, serum KL‐6 was reported to predict pulmonary fibrosis followed by infection with SARS‐CoV‐2 10,22 and serum SP‐D was reported to be useful for distinguishing pandemic influenza A (H1N1) from COVID‐19 in patients who required mechanical ventilation 23 .…”
Section: Discussionmentioning
confidence: 79%
“…A few studies have looked at the sensitivity, specificity, and predictive values of sKL-6 in COVID-19. Yamaya et al found a sensitivity of 83.3% and a specificity of 90.5 (AUC 0.89) to predict respiratory worsening with a sKL-6 cutoff point of 684 U/ml in 356 patients with sKL-6 determinations ( 26 ). Interestingly, they found a statistical association between baseline, peak, and Δ sKL-6 levels with severe illness and survival.…”
Section: Discussionmentioning
confidence: 99%